Control de constitucionalidad sobre resoluciones jurisdiccionales - Rojas Ortega, Alex (2014)
The Constitution establishes that jurisdictional acts are not susceptible to constitutional impugnation. However, the Code of Contentious Administrative Procedure has opened the possibility to submit jurisdictional resolutions to the cassation judge for constitutional control. This evidently extends people ́s opportunities to defend their rights and interests in Court of Law of the Republic.